Characteristics of superinfections during treatment with tigecycline. (3rd March 2016) - Katsiari, Maria; Ntorlis, Kyriakos; Nteves, Ioannis; Roussou, Zoi; Platsouka, Evangelia D; Maguina, Asimina
Abstract : Tigecycline has a broad-spectrum in vitro activity against Gram-positive and Gram-negative bacteria, including multidrug-resistant (MDR) strains. However, some Gram-negative bacteria are intrinsically resistant or have reduced susceptibility to tigecycline. We performed a prospective, observational study of 43 patients who received tigecycline as the treatment for serious infections due to MDR Gram-negative microorganisms, to evaluate superinfections. In 60.5% of our patients, tigecycline-resistant (T-R) Gram-negative microorganisms were isolated, representing superinfection in 37.2% and colonization in 23.5%. Pseudomonas aeruginosa was the predominant pathogen (48.4%) followed by Providencia stuartii, Proteus mirabilis and Stenotrophomonas maltophilia . Median time elapsed between tigecycline prescription and isolation of T-R pathogens was 7 days. The 16 superinfections consisted of ventilator-associated pneumonias (43.75%), catheter-related bloodstream infections (37.5%), intra-abdominal infections (12.5%) and urinary tract infection (6.25%). Attributed mortality to superinfections was 31.25%. The comparison of various potential risk factors for isolation of T-R microorganisms did not reveal statistically significant results.